Effectiveness of Cutting and Tailoring Trainings Organised by Krishi Vigyan Kendra for Scheduled Caste Women - Bala, Kiran; Varma, S K; Jain, Vinita (Indian Journal of Extension Education, 2020)
Cutting and tailoring is one of the avenues for self-employment which requires less of basic and technical education, minimum infrastructure and moderate financial needs. Proficiency in the art of cutting and tailoring is an essential prerequisite in clothing construction, It is very important to know the techniques of cutting and tailoring for producing attractive garments. The present study analysed the effectiveness of trainings imparted by Krishi Vigyan Kendra, Sadalpur on cutting and tailoring. Among the training programme designs of the garment was very useful with maximum training effectiveness index. The training on surface enrichment (83.61)and cutting of garments (82.78) was useful among the respondents with a marginally TEI score. Respondents were found to be highly satisfied with training programme. It indicated that respondents were highly satisfied about the subject matter taught/covered and quality of trainer made available to them during the training programme.